Utilization of Image Processing to Detect Hair Length According to SOP at IPB Vocational School Using Region-Based Segmentation - Alya Putri Salsabila; Achmad Syahmi Rasendriya; Muthia Nurul Sa'adah; Wahyu Mustika Aji; Rizky Fadlurohman; Endang Purnama Giri; Gema Parasti Mindara (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study utilizes image processing technology to detect student hair length in accordance with the Standard Operating Procedures (SOP) at IPB Vocational School. Manual supervision is often inefficient and prone to subjectivity, leading to the development of an automated detection system using a region-based segmentation approach. This method identifies the forehead area as a reference point, where hair is considered long if it exceeds specified limits. The system is implemented in a web-based application called Rambot, enabling students to verify their compliance with SOPs more easily. This technology aims to improve the accuracy and consistency of hair length monitoring.